Status of occlusal contact during sleep bruxism in patients who visited dental clinics – A study using a Bruxchecker®. Issue 3 (4th May 2018) - Tago, Chikataka; Aoki, Satoshi; Sato, Sadao
Abstract: Objective: Bruxism-induced mechanical load causes various dental problems, and its treatment is challenging. The present study analyzed upper and lower tooth contacts to determine actual occlusal contact during sleep bruxism. Methods: Tooth contact patterns were analyzed in 49 patients attending dental clinics, using a Bruxchecker®, cephalograms, and condylographs. Results: Approximately 80% of individuals demonstrated contact from the anterior teeth to the molar region (ICPM); about 96% had mediotrusive grinding and contact. The tooth contact area increased with the flatness of the anterior occlusal plane. The ratio of the contact area of the anterior teeth to the overall tooth contact area increased with overbite. Bilateral ICPM and mediotrusive contact patterns were associated with a high frequency of temporomandibular disorder symptoms, clicking, and/or pain. Discussion: The tooth contact area, anterior occlusal plane, and overbite are closely related, suggesting that tooth contact with the anterior teeth should be controlled with occlusal therapy.